Many names - many shapes: the war goddess in early Irish literature - with reference to Indian texts: a study in the phenomenology of religion - Bauer-Harsant, Ursula (The University of Edinburgh, 1996)
A quote from the Rees brothers book 'Celtic Heritage', comparing one of the Irish war -goddesses to the Indian Kali has provided the first impulse for this thesis. In the course of the study it emerged that the Indian material would be most useful in shedding further light on the Irish figures rather than to undertake a fully developed comparison.

When studying the Irish texts it soon becomes apparent that the war- goddesses cannot be seen in isolation but only in relationship with a male hero.Two heroes have extensive dealings with the war- goddesses, Cú Chulainn, the famous hero of Ulster, and the Dagda of the Túatha Dé Danann. Cú Chulainn generally benefits from the activites of the Badb, the screeching battle crow, while the Morri gan displays a relentless hostility towards him One important fact which emerges from these stories is the existence of a deap- seated similarity between the great hero and the otherwordly females which becomes particularly obvious when studying the various animal shapes the latter appear in. On the whole, the war -goddesses reveal themselves to be elusive, many -shaped figures who attack the hero's courage and inner strength rather than challenging him physically. They are not interested in questions of allegiance though this changes as time goes by, with later texts showing a different perspective.

The relationship between the Morrigan and the Dagda in Cath Maige Tuired takes a different form. Here, a powerful male figure who incorporates both life -giving and destructive aspects within his nature turns the destructive and chaotic potential personified by the Morrigan into more controlled channels so that she benefits his own people. Through his agency she becomes a powerful influence in the battle against the Fomorians. Figures who resemble the war -goddesses closely are investigated such as Washers at the Ford, death- messengers, hags and other hostile females.Variations on familiar themes and developments over time can be observed.It seems that very often the male hero determines the role of the otherwordly female and the later texts show a marked decline of the latter. Comparison with Indian evidence is prompted by the curious fact that although male figures are the protagonists of war in both cultures, it is female figures who emerge most clearly as the personifications of death and destruction.The question is asked whether any common features emerge which may explain this phenomenon and lead to a typology of female figures of death and destruction. An investigation of Kali's story reveals that certain attitudes towards violence and destruction are indeed similar, and that certain methods of containing this dangerous force in female shape find echoes in both traditions. However, the details as to behaviour, strategy, appearance, etc. show marked differences. It is concluded that comparison with Kali throws certain features of the Irish goddesses into sharper relief which may not have been possible otherwise. Any claim to seeing true similarities has to remain very tenuous indeed.